Views on technology development and transformation into Intelligence - Tiberiu Tanase,; Violeta Ioana Nagat, (Technium Social Sciences Journal, 2020)
During recent years the international environment has shown an increasing instability and more dangers and threats. All actors have to adapt their strategies to this new context, for being prepared to compete successfully with. In these conditions, intelligence’s role is to prevent threats deriving from the use of new technologies. One way of doing that consists in the transformation process of intelligence. Intelligence has to adapt to new challenges so as to provide policy makers and military information in order to make decisions for countering the cyber threats.